Haikyu!! 10 Hinata and Kageyama - Furudate, Haruichi, 1983-; Beck, Adrienne (San Francisco, CA : VIZ Media, LLC, 2021)
"Ever since he saw the legendary player known as "the Little Giant" compete at the national volleyball finals, Shoyo Hinata has been aiming to be the best volleyball player ever! Who says you need to be tall to play volleyball when you can jump higher than anyone else? After losing his first and last volleyball match against Tobio Kageyama, "the King of the Court," Shoyo Hinata swears to become his rival after graduating middle school. But what happens when the guy he wants to defeat ends up being his teammate?!"--Back cover.
"Parental Advisory: Haikyu!! is rated T for Teen and is recommended for ages 13 and up for mild language"--Page facing t.p.
"This book reads from right to left"--Back cover.
Translated from the Japanese.
School Library Journal
School Library Journal, December 2016
Young Adult
Keywords: Students -- Comic books, strips, etc. -- Juvenile fiction; Teenage boys -- Comic books, strips, etc. -- Juvenile fiction; Volleyball players -- Comic books, strips, etc. -- Juvenile fiction; Students -- Fiction; Teenage boys -- Fiction; Volleyball players -- Fiction; Manga; Students -- Comic books, strips, etc. -- Fiction; Teenage boys -- Comic books, strips, etc. -- Fiction; Volleyball players -- Comic books, strips, etc. -- Fiction; Graphic novels; Sports comics